Implementation of the Tax Law on the Imposition of Tobacco Products Tax in the Bintan Free Trade Zone - Vicky Fadian; Isnaini Isnaini; M. Citra Ramadhan (Asian Journal of Social and Humanities, 2023)
This research was conducted to determine how the regulation and application of the law on the imposition of cigarette excise in the Bintan FTZ (Free Trade Zone) and how the Tanjungpinang Customs Office oversees the circulation of illegal cigarettes in the Bintan FTZ. This research is empirical juridical research with a descriptive nature. It is known that the legal arrangements regarding the imposition of cigarette excise at FTZ Bintan refer to Law Number 39 of 2007, Law Number 36 of 2000 as last amended by Law Number 44 of 2007, PP Number 41 of 2021, and Ministerial Regulation Finance Number 34/PMK.04/2021. The application of this law can be seen from the substance of the law, where the law on the imposition of cigarette excise in the Bintan FTZ is subject to cigarette excise. From the legal structure, law enforcement overseeing illegal cigarette distribution in the Bintan FTZ consists of Customs, TNI, Polri, the Attorney General's Office, the Judiciary, and the Civil Service Police Unit as supporters. In terms of legal culture, the decline in the results of controlling illegal cigarettes in the Bintan FTZ shows that the level of public trust in the provisions of the Excise Law has begun to increase. Supervision carried out by Tanjungpinang Customs and Excise is carried out in 2 (two) ways, namely preventive and repressive.